2021
DOI: 10.1101/2021.03.23.436648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phospholipidosis is a shared mechanism underlying thein vitroantiviral activity of many repurposed drugs against SARS-CoV-2

Abstract: Repurposing drugs as treatments for COVID-19 has drawn much attention. A common strategy has been to screen for established drugs, typically developed for other indications, that are antiviral in cells or organisms. Intriguingly, most of the drugs that have emerged from these campaigns, though diverse in structure, share a common physical property: cationic amphiphilicity. Provoked by the similarity of these repurposed drugs to those inducing phospholipidosis, a well-known drug side effect, we investigated pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
(109 reference statements)
0
9
0
Order By: Relevance
“…Sigma-1 and sigma-2 receptors, both of which appear to play roles in cholesterol transport ( 66 , 67 ), were identified as potential targets in SARS-CoV-2-human protein-protein interaction screens ( 68 , 69 ). In screens of repurposed drugs, it has been observed that there was a strong correlation between antiviral efficacy against SARS-CoV-2 and the magnitude of phospholipidosis in vitro ( 70 ). However, none of the lead compounds tested exhibited significant antiviral activity in vivo , underscoring the need for additional research to translate these in vitro observations into a useful therapeutic approach in humans.…”
Section: Lipids In Viral Replicationmentioning
confidence: 99%
“…Sigma-1 and sigma-2 receptors, both of which appear to play roles in cholesterol transport ( 66 , 67 ), were identified as potential targets in SARS-CoV-2-human protein-protein interaction screens ( 68 , 69 ). In screens of repurposed drugs, it has been observed that there was a strong correlation between antiviral efficacy against SARS-CoV-2 and the magnitude of phospholipidosis in vitro ( 70 ). However, none of the lead compounds tested exhibited significant antiviral activity in vivo , underscoring the need for additional research to translate these in vitro observations into a useful therapeutic approach in humans.…”
Section: Lipids In Viral Replicationmentioning
confidence: 99%
“…In this study, 100 µM HCQ induced neutral lipid accumulation in HepaRG cells incubated without fatty acid accumulation. However, to the best of our knowledge, HCQ-induced accumulation of hepatic triglycerides (i.e., steatosis) does not seem to occur in treated patients, contrary to phospholipid accumulation (i.e., phospholipidosis), which is common with this cationic amphiphilic drug [ 16 , 41 ]. Hence, our data suggest that only a few susceptible patients might be at risk for HCQ-induced steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with the hydrophobic nature of DT-061 and the fact that we see DT-061 forming small structures in cells attracting the Golgi marker. Tricyclic heterocyclic compounds can have a profound impact on lipids and indeed methylene blue, which belongs to this class of molecules, has been used to stain the Golgi in cells [3741]. We acknowledge the extensive studies conducted by Leonard et al (2020) to analyse the interaction between DT-061 and PP2A-B56α complexes.…”
Section: Discussionmentioning
confidence: 99%